Islamophobia in American Against Muslims in “My Name is Khan” Film - Rahim, Amirah Asmaniar Muslimah; Nur, Muh Safar; Halim, Abd. (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2024)
This research discusses Islamophobia that occurs in America in the film